Organic and Inorganic Fertilizers application on the Growth, Yield and Artemisinin Content of Artemisia Annua L. in the Humid Tropics of Ghana. - Yeboah, Stephen (2011)
A thesis submitted to the Department of Crop and Soil Sciences, College of Agriculture and Natural Resources, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the Award of Master of Science degree in Agronomy (Crop Physiology).